Emerging Topological Multiferroics from the 2d Rice-Mele Model - Allende-Prieto, S (Nature Research, 2024)
We introduce a two-dimensional dimerized lattice model that reveals a remarkable feature: the emergence of a complex, non-trivial topological multiferroic phase marked by zero Berry curvature and a significant Berry connection that influences the model’s bulk topology. This model extends the one-dimensional Rice-Mele Hamiltonian model to explore polarization-dependent topological properties in a 2D Su-Schrieffer-Heeger lattice, providing a detailed framework for studying the impact of symmetry-breaking and spatially varying potentials on electronic and spin properties. The findings are particularly relevant for spintronics, offering a foundation for topologically robust and electrically controlled spin-conducting edge states, with implications for developing advanced spin-dependent transport devices. © The Author(s) 2024.